IMPLEMENTASI DIPLOMASI KEBUDAYAAN INDONESIA DI JEPANG MELALUI RUMAH BUDAYA INDONESIA (RBI) PERIODE 2017-2019 - Asep Kamaludin (Journal of Diplomacy and International Studies, 2019)
This paper aim to analyze about the Implementation of Indonesian Cultural Diplomacy in Japan through Rumah Budaya Indonesia (RBI) Period 2017-2019. In this era, culture has become an important issue that deserves to be discussed. Besides being national identity of a country, culture also used as a instrument to achieve the country's national interests. Currently, Indonesia is one of the countries that uses cultural diplomacy as an effort to achieve its national interests. In this case, the Ministry of Education and Culture established Rumah Budaya Indonesia (RBI) in Japan to reinforce Indonesian cultural diplomacy. The result of this research show that the influential Rumah Budaya of the positive image of Indonesia and the increasing number of tourist to Indonesia. This paper uses the diplomacy theory, the concept of cultural diplomacy and the concept of a Rumah Budaya.